Step 1. Identify the variable.
Step 2. Write an algebraic equation.
Step 3. Solve the equation.
Step 4. Answer the equation.
Step 5. Check answer.
Hope this helps...?
Answer:
bd=cc=oc2
Step-by-step explanation:
a f(a) is the function f(x) where x is replaced by a.
So we have
(3x^2 + x + 3 - (3a^2 + a + 3)) / ( x - a)
= (3x^2 - 3a^2 + x - a) / (x = a) Answer
b (3(x + h)^2 + x + h + 3 - (3x^2 + x + 3)) / h
= (3x^2 + 6xh + 3h^2 + x + h - 3x^2 - x - 3) ) / h
= (6xh + h + 3 h^2) / h
= 6x + 3h + 1 Answer
The answer for this is 10